2009
DOI: 10.1074/mcp.m900135-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Nature of Glycan Alterations on Specific Proteins in Pancreatic Cancer Patients Revealed Using Antibody-Lectin Sandwich Arrays

Abstract: Changes to the glycan structures of proteins secreted by cancer cells are known to be functionally important and to have potential diagnostic value. However, an exploration of the population variation and prevalence of glycan alterations on specific proteins has been lacking because of limitations in conventional glycobiology methods. Here we report the use of a previously developed antibody-lectin sandwich array method to characterize both the protein and glycan levels of specific mucins and carcinoembryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
118
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 43 publications
4
118
0
Order By: Relevance
“…Similarly, changes in the expression of long chains of lactosamine (polyLacNAc) have also been reported to be associated with cancer (15). Likewise, terminal modifications of glycans on the cancer cell surface, such as fucosylation, give rise to the presence of Lewis and sialyl Lewis antigens that have been implicated in tumor progression and metastasis (22)(23)(24)(25)(26). These aberrant glycosylations play a significant role in malignant transformation and therefore afford a valuable opportunity to exploit cancer-specific protein glycosylation markers for prognosis and diagnosis (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, changes in the expression of long chains of lactosamine (polyLacNAc) have also been reported to be associated with cancer (15). Likewise, terminal modifications of glycans on the cancer cell surface, such as fucosylation, give rise to the presence of Lewis and sialyl Lewis antigens that have been implicated in tumor progression and metastasis (22)(23)(24)(25)(26). These aberrant glycosylations play a significant role in malignant transformation and therefore afford a valuable opportunity to exploit cancer-specific protein glycosylation markers for prognosis and diagnosis (16).…”
mentioning
confidence: 99%
“…In fact, MS identification and measurement of glycans are being pursued as a structurallyinformative approach as opposed to the clinically-established immunological assays (23)(24)(25) or arrays (26). Several quantitative glycomic profiling studies have identified N-glycan changes that were statistically elevated in ovarian cancer patients' plasma (17,(27)(28)(29).…”
mentioning
confidence: 99%
“…In the further pursuit of alternative molecular markers, the patterns of glycosylation have been studied in sera of patients with pancreatic cancer using antibody-and lectin-based sensors (7,8). A similar approach has been used to study pancreatic cyst fluids, targeting representative glycans on prominent candidate glycoprotein markers, including several of the mucins and carcinoembryonic antigen-related cell adhesion molecules.…”
mentioning
confidence: 99%
“…A glycoform of MUC5AC, one that binds the lectin wheat germ agglutinin (WGA), was almost exclusively found in the mucinous cysts and was a better biomarker than the MUC5AC protein measured over all glycoforms. Furthermore, the glycosylation patterns in pancreatic cysts were different from those we found in pancreatic ductal adenocarcinomas (21,22).…”
mentioning
confidence: 37%